Pseudocontingencies in consumer choice: preference for prevalent product categories decreases with decreasing set quality - Vogel, Tobias; Kutzner, Florian (Journal of behavioral decision making, 2017)
Building on theorizing about contingency inferences, the present research deals with the impact of product category prevalence on consumer choice. We argue that a category's prevalence in the choice set can signal high quality, but the validity depends on the aggregate quality of the choice set. With ever more low-quality products in the set, high prevalence should increasingly signal poor rather than high quality. When choosing from a poor-quality set, choices should thus favor products from the rare category. In four experiments, we show that poor-quality sets increase the proportion of consumers choosing products from a rare category. Furthermore, we show that these effects increase when base rates of a category and quality become more extreme. Finally, Experiment 4 shows that contingency inferences partly mediate the effect of set quality on choice. The results extend previous research on contingency inferences, indicating the adaptive use of base-rate information in consumer decision making. Copyright © 2017 John Wiley & Sons, Ltd.